1990
DOI: 10.1002/j.2161-0045.1990.tb00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Self‐Ratings of Abilities and Skills

Abstract: Students' ratings of their abilities and skills were examined in relationship to self‐esteem and to their ratings of same‐gender peers. Participants were 112 students (59 women and 53 men) who were administered the Rosenberg (1965) self‐esteem scale and a questionnaire assessing self‐ratings of 14 general abilities and 30 specific skills, as well as peer ratings of the skills. Results indicated that (a) gender differences were observed on 3 of the 14 general abilities, (b) there were significant interactions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…However, very few gender differences in confidence were found within occupational group; the small differences that were found were for confidence areas other than the one characterizing their occupation. Using a slightly different approach, Swanson and Lease (1990) found that college men rated themselves and their same-sex peers higher than college women rated themselves and their same-sex peers only on the Realistic theme. Women rated themselves and their same-sex peers higher than men rated themselves and their same-sex peers only on the Social theme.…”
Section: Self-efficacy and Social Cognitive Theorymentioning
confidence: 94%
See 4 more Smart Citations
“…However, very few gender differences in confidence were found within occupational group; the small differences that were found were for confidence areas other than the one characterizing their occupation. Using a slightly different approach, Swanson and Lease (1990) found that college men rated themselves and their same-sex peers higher than college women rated themselves and their same-sex peers only on the Realistic theme. Women rated themselves and their same-sex peers higher than men rated themselves and their same-sex peers only on the Social theme.…”
Section: Self-efficacy and Social Cognitive Theorymentioning
confidence: 94%
“…Gender differences have been reported in self-efficacy for the six Holland (1997) themes as well Parsons & Betz, 1998;Swanson & Lease, 1990). found that college men reported more confidence than college women in the Realistic, Enterprising, Investigative, and Conventional themes.…”
Section: Self-efficacy and Social Cognitive Theorymentioning
confidence: 98%
See 3 more Smart Citations